SINDROMA NEFROTIK RELAPS DENGAN ANEMIA PADA ANAK - Aty Firsiyanti; Alyaa Nabiila; Hava Ayu Millenia (Surabaya Biomedical Journal, 2024)
Introduction: Nephrotic syndrome is a kidney disease characterized by edema, hypoalbumin, hyperlipidemia, and massive proteinuria. The prevalence in children ranges from 2-7 cases per 100,000 children under 18 years of age and most experience relapse. The prognosis for nephrotic syndrome in which it relapses will increase the risk of other complications. Case report: A 4-year-old boy was diagnosed with nephrotic syndrome characterized by anasarca edema, hypoalbumin, hypercholesterolemia, and massive proteinuria. The patient was included in the relapsed nephrotic syndrome category because he had previously been diagnosed with nephrotic syndrome and had experienced remission. Currently, the therapy that has been given consists of bed rest, fluid restriction, administration of the diuretic furosemide and administration of the oral steroid prednisone again. In addition, the patient experienced anemia due to complications from nephrotic syndrome and a PRC transfusion was planned. Discussion: Nephrotic syndrome is a kidney disease that often occurs in children. The prevalence is 15 times more common in children than adults. As many as 60-70% will experience a relapse. Relapsing nephrotic syndrome requires longer duration of corticosteroid therapy. Anemia is one of the complications in relapsing nephrotic syndrome.